Foraging behavior interactions between two non-native social wasps, Vespula germanica and V. vulgaris: implications for invasion success? - Pereira, Ana J. (2016)
Fil: Pereira, Ana J. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina.